Minimal decrease in triathlon running performance compared to isolated running performance is important for sprint triathlon success - Takahashi, K.; Nabekura, Y. (Journal of Science and Cycling, 2021)
A strategy to improve running performance in a triathlon is minimizing fatigue from the preceding exercise. However, little is known about performance decrement, or the degree to which it changes, in triathlon running (TR) compared to isolated running (IR). This study examined the decrease in TR performance compared to IR performance and the degree of change as determined from sprint triathlon competition results. The data were obtained from the official result times of certification competition events from 2013 to 2016 (IR) and elite categories participating in the Asia Cup sprint triathlon from 2013 to 2016 (TR). Data of 236 athletes who finished IR and TR in the same year were analysed. The average performance was significantly worse in TR than in IR (p < 0.01), and the effect size in a paired Wilcoxon test was large, regardless of competition years and sex. There were also large inter-individual differences in the performance decrement in TR compared with IR. The overall triathlon performance and performance decrement in TR compared with IR showed significant correlation (Spearman`s rho = 0.47-0.76, p < 0.05). In conclusion, TR performance was worse than the IR performance and the degree varied widely inter-individual. The smaller the performance decrement in TR compared with IR, the more likely the athlete is to succeed in the sprint triathlon.